Common ground on hostile turf : stories from an environmental mediator - Moore, Lucy, 1944- (Island Press, 2013)
"As an environmental mediator, Lucy Moore has spent the past quarter century resolving conflicts that appeared utterly intractable. Here, she shares the ten most compelling stories of her career"--